Faktor-faktor yang mempengaruhi Kinerja Usaha Mikro: Penggunaan Dana BPUM , Penggunaan Software Akuntansi dan Human Capital - Cut Zia Auralia; Cris Kuntadi; Rachmat Pramukty (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence micro business performance, namely the use of BPUM funds, the use of accounting software and human capital, a literature study on accounting information systems. The purpose of this paper is to produce a hypothesis about the influence between variables that can be used in further research. The results of this literature review article are 1) The use of BPUM funds affects the performance of micro businesses; 2) the use of accounting software affects the performance of micro businesses; and 3) human capital affects the performance of micro businesses.